Caracterização físico-química do óleo e do biodiesel de Crambe abyssinica Hochst - Jasper, Samir Paulo [UNESP]; Biaggioni, Marco Antônio Martin [UNESP]; Silva, Paulo Roberto Arbex [UNESP] (Fundacao Educational de Ituverava, 2013)
Currently, the production of biodiesel in the world is growing so rapidly, this interest and demand for biodiesel promote an increase in demand for raw materials, or lipids. Biodiesel is a substitute for diesel oil obtained by transesterification, acid or base, of the lipids present in oils and fats. The Crambe abyssinica Hochst is species plant that has attracted interest of Brazilian producers due to oil content, rusticity and mechanized cultivation, mainly as a crop of winter it becomes an option for most farmers in this period. This study aimed to characterize physical-chemical oil and biodiesel from Crambe abyssinica Hochst, in accordance with Resolution n° 7 of the ANP. The analysis of fatty acids of oil Crambe showed high concentration of unsaturated fatty acids, which may not be suitable for the use of biodiesel in very cold regions, where it is used pure or in mixtures with diesel in large proportions. The biodiesel produced from Crambe abyssinica Hochst be revealed within the standards established by the National Agency of Petroleum, Natural Gas and Biofuels.

Atualmente, a produção de biodiesel no mundo vem crescendo de forma acelerada, este interesse e demanda por biodiesel promovem um aumento da demanda por matéria-prima, ou seja, lipídios. O biodiesel é um substituto do diesel de petróleo obtido pela transesterificação, ácida ou básica, dos lipídios presentes nos óleos e gorduras. O Crambe abyssinica Hochst é uma espécie vegetal que tem despertado interesse dos produtores brasileiros, devido ao teor de óleo, rusticidade, cultivo mecanizado e, principalmente, por ser uma cultura de inverno tornando, assim, mais uma opção ao agricultor neste período. Objetivou-se, neste trabalho, a caracterização físicoquímica do óleo e do biodiesel proveniente do Crambe abyssinica Hochst, de acordo com a Resolução n° 7 da ANP. A análise de ácidos graxos do óleo do crambe indicou elevada concentração de ácidos graxos insaturados, o que pode não ser adequado para o uso do biodiesel em regiões muito frias, caso utilizado puro ou em misturas elevadas com óleo diesel. O biodiesel produzido a partir do Crambe abyssinica Hochst revelou estar dentro das normas estabelecidas pela Agência Nacional do Petróleo, Gás Natural e Biocombustíveis.
Physical-chemistry characterization of oil and biodiesel from Crambe abyssinica Hochst
Keywords: Biofuel; Alternative fuel; Fatty acids; Biocombustível; Combustível alternativo; Ácidos graxos